Síntese hidrotérmica assistida por micro-ondas do CaTiO3 puro e dopado com samário e sua caracterização óptica e morfológica - Pinatti, Ivo Mateus (2014)
The ATiO3 (A = Pb, Ca, Sr, and Ba) perovskite have attracted considerable attention and constitute one of the most important class of mixed oxides. It presents various applications owing to their physical properties and has been extensively studied as candidates for electro-optical devices. Pure Calcium Titanate (CT) and Samarium doped Calcium Titanate Ca1-xSmxTiO3 (x = 0,5%, 1,0%, 3,0% and 5,0% molar ratio of Sm3+ ions) powders were synthesized by hydrothermal microwave method (HTMW) at 140 °C for 16 min resulting in the samples CT:Sm (0,5%), CT:Sm (1,0%), CT:Sm (3,0%) and CT:Sm (5,0%), respectively. The HTMW method appears to be an efficient method to prepare the luminescence materials using low temperatures and very short reactional times. Sm3+ ion was introduced into the perovskite lattice aiming to study the synthesis, photoluminescence emissions and morphological properties of these powders. X-ray diffraction (XRD) patterns present a single phase indexed as Pbnm space group in a typical orthorhombic CaTiO3 (CT) structure which prove long-range order. Micro-Raman (MR) spectra of the samples indicated the characteristics vibrational modes, while UV-vis measurements showed changes in the optical absorbance behavior of CT samples compared to CT:Sm. The existence of two small absorbance bands at 406 and 603 nm suggests the presence of Sm3+ in the CT lattice, confirmed by excitation and photoluminescence emission spectra. Photoluminescence (PL) spectra show Sm3+ emission lines ascribed to the Sm3+ transitions from 4G5/2 excited states to 6HJ (J = 5/2, 7/2, 9/2 and 11/2) states in CT:Sm powders excited at 406 nm, that was noticed at, respectively 567, 603, 648 and 713 nm. Among the samples, the most intense photoluminescence results were observed for the CT:Sm (1,0%) sample. Field Emission Gun -Scanning Electron Microscope (FEG-SEM) showed micro-cubes shape with dimensions around 3,0 μm and were not affected by the Sm3+ concentrations considered here. EDSX results confirmed the composition of the samples. The Commission International d Eclairage (CIE) chromaticity coordinates of the as prepared CT:Sm samples were determined and confirm these materials as promising candidates for applications in the visible red-orange range spectra.